From principles to practice: distributive justice and the role of perceived inequality in reward allocation - Gilgen, Sandra; Zangger, Christoph (Frontiers in Sociology, 2025)
How do people balance competing principles of distributive justice when allocating limited goods? This study applies a novel methodological approach—distributional survey experiments (DSEs)—to examine how people weigh merit, need and equality considerations when deciding how to distribute salaries to people with different ascriptive characteristics and occupations. In the DSE, that we embedded in a representative Swiss survey, respondents were asked to allocate a fixed sum among three hypothetical hospital employees with experimentally varying attributes. This design not only allows us to identify causal factors behind allocation decisions but also captures the underlying interdependence involved in questions of distributive justice. What is more, we can examine drivers of the resulting inequality directly through the allocated salaries. The analyses reveal that although merit-based considerations (occupation, job dedication) have the strongest influence on allocation decisions in the workplace context, need (e.g., having dependent children) and discrimination (e.g., against women and ethnic minority men) also shape outcomes. Moreover, respondents who perceive actual income inequality as too high distribute resources more equally. Conversely, higher-income and higher-status respondents produce more unequal distributions. Our findings highlight how distributional preferences are shaped by justice principles, social background, and inequality perceptions. The study contributes methodologically and substantively to justice and inequality research by linking normative principles and experienced conditions to actual allocation behavior and the distributional consequences thereof.